2020
DOI: 10.1111/mam.12195
|View full text |Cite
|
Sign up to set email alerts
|

Global patterns in seed germination after ingestion by mammals

Abstract: 1. Mammals play an important role in seed germination through the ingestion of fruits and seeds. Since seed germination is a basic step in seedling recruitment, understanding how mammals affect germination improves our understanding of the effect of loss of mammal populations on the dynamics of plant communities. 2. We used meta-analytical methods to describe global patterns in the effect of seed ingestion by mammals on seed germination success and rate. We collected data from 154 studies that included 115 mam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…After gut passage, the germination rate of seeds was not different from that of uningested seeds for A. mangostanus , C. album and P. oleracea . This was also in agreement with the general pattern after their passage through the gut of the family Cervidae, with non-significant lower seed germination rate (Torres et al, 2020). After passing the gut, seed recovery and germination rate decreased for most species.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…After gut passage, the germination rate of seeds was not different from that of uningested seeds for A. mangostanus , C. album and P. oleracea . This was also in agreement with the general pattern after their passage through the gut of the family Cervidae, with non-significant lower seed germination rate (Torres et al, 2020). After passing the gut, seed recovery and germination rate decreased for most species.…”
Section: Discussionsupporting
confidence: 90%
“…In the transfer phase, mastication and gut passage affect seed germination and determine the quality of seed dispersal (Baltzinger et al, 2019). According to a recent meta-analysis study, the effects of gut passage on seed germination varied among animal species (Torres et al, 2020). Also, the seed germination rates after gut passage differ according to ingested plant species (Mancilla-Leytón et al, 2011, 2013; Torres et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a global study, it has been proposed that mammals have a positive effect as enhancers of seed germination, although some groups, such as rodents, cause low seed germination and high mortality after ingestion. Particularly for Fabaceae seeds, mammals do not have a significant effect on germination (except in the case of Primates; Torres et al, 2020). In contrast to this general study, we found that the quality of seed treatment by D. patagonum , the rodent of our study, was similar in its high seed recovery to L. gymnocercus , and similar in its high seed germination to L. guanicoe .…”
Section: Discussionmentioning
confidence: 99%
“…Biodiversity is essential to maintain Ecosystem Services (ES) (Cardinale et al 2012), and mammals are particularly important providers of ES as they comprise a highly diversified group that play key and disproportionate roles in ecosystems (Davidson et al 2012, Sarasola et al 2016, from pollination (Ratto et al 2018) and seed dispersal (Torres et al 2020) to top-down population control by predators (Ripple et al 2014) and soil engineering (Villarreal et al 2008, Davidson et al 2012, Villar et al 2020.…”
Section: Introductionmentioning
confidence: 99%